PELATIHAN FOTOGRAFI DAN VIDEOGRAFI SECARA VIRTUAL DALAM PENINGKATAN KEMAMPUAN DIRI PADA PANDEMIC COVID-19 - Erlyana, Yana; Hansen, Hendia (Jurnal Pengabdian dan Kewirausahaan, 2021)
ABSTRACT                 The state of the Coronavirus Disease 2019 (Covid-19) pandemic forces people to be more adaptive. This includes self-development so that it can reduce the negative impacts that can arise within oneself. Coupled with the development of information technology is increasingly rapid until now and the technologies that support it continue to be developed. People take a lot of time to try to improve their technology-related skills such as photography and videography. In its development, both photography and videography have undergone many changes from manual to digital until a few moments ago a trend emerged where due to the pandemic situation which required us to keep our distance or what is known as social distancing, the trend of virtual photography and videography emerged. So that this community service activity takes place online with participants from students / I SMK Bonavita Tangerang. In this community service consists of two parts, the first is the provision of material and an understanding of non-virtual and virtual shooting procedures, so that participants understand the basics of shooting from pre-production, production to post-production, in which the material is given direct practical examples. conducted by the two speakers. The final result of this community service activity went well and was responded well by the participants. Participants receive material on photography and videography competencies that have been adapted to be used in the current pandemic situation.